The moon dragon - Abbott, Tony, 1952-; Merrell, David, 1973-; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 2006)
Eric and his friends must rescue their parents and other adults in their hometown from Gethwing, the moon dragon.
"A Little Apple paperback."
G4
Keywords: Droon (Imaginary place) -- Juvenile fiction; Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Droon (Imaginary place) -- Fiction; Dragons -- Fiction; Magic -- Fiction; Fantasy; Children's stories; Fantasy fiction